Simple Additive Weight Method in Determining Promotion Target for New Student Admission at STMIK Sinar Nusantara - Dziky Ridhwanullah; Hartanto, Budi; Raharja, Bayu Dwi (Ittishal Educational Research Journal, 2024)
Each university will hold PMB (New Student Admission) activities. Similar to STMIK Sinar Nusantara, which is one of private universities in Surakarta, these events are held annually to draw in individuals who wish to pursue higher education. This is a very significant activity for a private university, with a new improvement target each year. At a private university, the number of new students is crucial because it is the primary source of funding. Activities of New Student Admission (PMB) at STMIK Sinar Nusantara have shown a decreasing tendency for a number of years. Institutional development and instructional activities will be impacted by this. One of the reasons is the widespread adoption of promotional targets that lack a scholarly foundation. Therefore, a decision support system is required to solve this issue. This study aims to assist policy makers in selecting appropriate promotion targets. The technique in this research is Simple Additive Weighting (SAW). The school promotion targets derived from the school ranking order and cluster classification are the outcomes of this study. With a score of 0.96, SMKN 1 Bulukerto School got the highest preference computation score. SAW method-based decision support system has been successful in identifying the appropriate promotional targets. The results of this research can be used by policy makers organizing activities of new student admission in promoting STMIK Sinar Nusantara to increase the number of new students.